The Requiem in the Age of Confessionalisation. A Review of The Book of Requiems vol. 2 - Simone Caputo (Muzyka)
The Book of Requiems (vol. 2), edited by David J. Burn and Antonio Chemotti, collects analytical musicological essays on Requiems composed between 1550 and  1650, drawing a comprehensive map of early modern polyphony for the liturgy of the dead, covering regions from Flanders to central Europe and from Italy to the Iberian Peninsula. This map facilitates the rediscovery of a significant portion of Catholic sacred music from the era of confessionalisation, including both celebrated masterpieces and lesserknown yet historically significant works of great beauty. Complementing this ideal map is a detailed catalogue of Requiems, which is a valuable and up-to-date research tool.